System identification of a six-legged semisubmersible subjected to wave loads through frequency domain analysis - Yew, G.Z. (2013)
Sea state conditions such as wind, wave and current vary in different ocean waters. Two similar offshore structures installed in two different ocean regions will yield different responses. Determining the transfer function of the structure is a system identification exercise that yields the structural response and behaviour given any sea state condition. The transfer function can be determined using available measured sea state data and structural response data. In this paper, a six-legged semisubmersible physical model is developed to a scale of 1:100 and is tested in a wave tank to measure its responses due to simulated random wave loads. The transfer functions of the semisubmersible model are then determined using the measured responses and the measured wave heights. Â© (2013) Trans Tech Publications, Switzerland.